Processo de laminação com resfriamento criogênico em ligas de magnésio para armazenagem de hidrogênio - Silva, Wágner Batista (Universidade Federal de São Carlos, 2017)
The use of metallic hydrides is a competitive alternative to the hydrogen storage in the liquid or gas states. The magnesium is cheap and forms the metal hydride with higher gravimetric capacity. In this work, the commercial magnesium and its alloys as AZ91 and ZK60+2.5%Mm were processed by two combined processes: ECAP+CR and ECAP+LTR. In processing by ECAP, route Bc was used with four passes at 300 °C and 9 mm/min of run speed. After ECAP, the samples were cold rolled in three routes different forms: (1) by cold rolling at room temperature (CR); (2) cold rolling with the immersion of the alloys in liquid nitrogen for a time of tree minutes starting from the first and after 5 passes (LTR 1/5); (3) cold rolling with the immersion of the alloys in liquid nitrogen for a time of tree minutes every pass (LTR 1/1). According to the results the processing combination of ECAP followed by CR and ECAP followed by LTR, an intense [002] texture peak was observed, mainly for commercial Mg. The results of MEV SEM and microtomography have shown that the cryogenic temperature processing resulted in more brittle materials, causing more cracking on bulk and clear interfaces than the conventionally cold rolled ones. A highly refined microstructure and an introduction of defects with favorable [002] crystallographic orientation for samples processed by ECAP followed by LTR samples resulted in higher hydrogen storage capacities without observation or with short incubation time.
Process of lamination with cryogenic cooling in magnesium alloys for hydrogen storage
Keywords: Magnésio; Hidrogênio; Magnesium; Hydrogen; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO